A High-Throughput Fluorometric Method for Quantitation of Besifloxacin Hydrochloride Using Microplate Reader - Abd El-Hay, Soad S; El-Sayed, Heba M (Current Pharmaceutical Analysis, 2018)
Objective: The present study describes the development and validation of a simple highthroughput method for the fluorometric determination of besifloxacin HCl in 96-microwell plates. Methods: The proposed method is based on the reaction between besifloxacin HCl and fluorescamine in borate buffer solution of pH 8.5 giving a highly fluorescent derivative that was developed simultaneously and measured at 471 nm after excitation at 353 nm. The different experimental conditions affecting the fluorescence reaction were carefully investigated and optimized. Results: The method showed linearity over the concentration range of 200-1000 ng/mL with low Limits Of Detection (LOD) and Quantitation (LOQ) of 8.47 ng/mL and 28.24 ng/mL, respectively. The Relative Standard Deviation (% RSD) and Relative Error (% RE) values did not exceed 3 % for precision and accuracy respectively. The developed high-throughput method was successfully applied for the determination of besifloxacin HCl in simulated tears and eye drops. Conclusion: The capability of the method for measuring micro-volume samples makes it convenient for handling a very large number of samples simultaneously. In addition, using micro-well plates can offer a safer and economic method for the determination of besifloxacin HCl in pharmaceutical dosage forms.
Keywords: Besifloxacin